A SURVEY OF INDONESIAN EFL UNDERGRADUATE STUDENTS' SELF-REGULATED MOTIVATION TO SPEAK ENGLISH - Dwika Salsabila; Ista Maharsi (ENGLISH, 2023)
Self-Regulated Motivation (SRM) is one of Self-Regulated Learning (SRL) aspect that focus only on motivation control or regulation. This study aims to identify college students' SRM levels to speak English and the difference between male and female. The participants were 92 English Language Department students of a private university in Yogyakarta. The data were collected through SRMIS-EFL questionnaire. The questionnaire consists of four factors (task value evaluation, regulation of learning environment, regulation of affect, and regulation of classroom environment) with 20 total items. A descriptive statistic was used to analyze students' SRM level and an independent sample t-test was also used to see the difference of SRM level between male and female students. The analysis of the data showed that generally students had a high SRM level. The highest factor was task value evaluation and the lowest was regulation of learning environment.  Related to gender, this study revealed that male and female students show a similar SRM levels and had no difference.